2020
DOI: 10.1093/scan/nsaa122
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning prompts sparser representations of conditioned threat in primary visual cortex

Abstract: Repeated exposure to threatening stimuli alters sensory responses. We investigated the underlying neural mechanism by re-analyzing previously-published simultaneous EEG-fMRI data from humans viewing oriented gratings during Pavlovian fear conditioning. In acquisition, one grating (CS+) was paired with a noxious noise, the unconditioned stimulus (US). The other grating (CS-) was never paired with the US. In habituation, which preceded acquisition, and in extinction, the same two gratings were presented without … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 74 publications
8
19
0
Order By: Relevance
“…Unlike neutral conditioning where the main effect is to strengthen the response magnitude, the main effect of aversive conditioning is to significantly reduce neural response magnitude and the prevalence of cue-evoked persistent activity within V1. Previous studies have demonstrated that in primary sensory areas, fear conditioning results in a "sparsification" of sensory responses (Gdalyahu et al, 2012;Yin et al, 2020). The network dampening caused by aversive conditioning we observe here is consistent with these previous reports.…”
Section: Cue-evoked Persistent Activity In the Presence Of Non-rewardsupporting
confidence: 93%
“…Unlike neutral conditioning where the main effect is to strengthen the response magnitude, the main effect of aversive conditioning is to significantly reduce neural response magnitude and the prevalence of cue-evoked persistent activity within V1. Previous studies have demonstrated that in primary sensory areas, fear conditioning results in a "sparsification" of sensory responses (Gdalyahu et al, 2012;Yin et al, 2020). The network dampening caused by aversive conditioning we observe here is consistent with these previous reports.…”
Section: Cue-evoked Persistent Activity In the Presence Of Non-rewardsupporting
confidence: 93%
“…It has been assumed that re-entrant projections from fear-relevant areas centered around the amygdala prompt short- and long-term adaptions in threat-related feature-specific neurons 9 , 51 . However, a recent study, exploiting the benefits of simultaneous fMRI-EEG analysis, showed that threat-related visuocortical changes were associated with neural activity in the ventral attention network, but not in the amygdala 52 . The ventral attention network, including the temporoparietal and inferior frontal cortices, is specialized on detecting behaviorally relevant, salient stimuli 53 .…”
Section: Discussionmentioning
confidence: 99%
“…A classical conditioning approach was used to pair one of three initially neutral pitches of a sine-wave tone with a loud noise. Three dependent variables with known sensitivity to generalization learning were considered: self-reported valence and emotional arousal in response to each pitch ( McTeague et al, 2015 ; Plog et al, 2022 ), as well as stimulus-induced reductions in parieto-occipital alpha power, a brain response linked to the attentive processing of aversively conditioned cues, auditory or visual ( Miskovic and Keil, 2012 ; Yin et al, 2020 ; Friedl and Keil, 2021 ). Self-reported symptoms on the MSS were used to quantify the intensity of Misophonia symptoms in each participant.…”
Section: Discussionmentioning
confidence: 99%
“…Parieto-occipital alpha-band power reduction has long been associated with responses to a salient external event, regardless of sensory modality ( Berger, 1929 ; Friedl and Keil, 2021 ). Recently, these changes have been shown to index aversive conditioning, including generalization learning ( Friedl and Keil, 2020 ; Yin et al, 2020 ). Consistent with the self-reported behavioral findings, we found that alpha-band power reduction showed pronounced activity patterns best fit by an all-or-nothing learning model across all participants at the predicted parieto-occipital regions where alpha power during rest is maximal.…”
Section: Discussionmentioning
confidence: 99%